VEP and PERG in patients with multiple sclerosis, with and without a history of optic neuritis - Janáky, M.; Jánossy, Á.; Horváth, G.; Benedek, G.; Braunitzer, G. (Documenta ophthalmologica, 2017)
Purpose Visual electrophysiology is routinely used to detect the visual complications of multiple sclerosis, but the analysis mostly focuses on visual evoked potential (VEP) and especially the P100 component. Our goal was to analyze the components and waveform alterations of VEPs and pattern electroretinograms (PERGs) in patients with multiple sclerosis (MS) with good vision. Methods The main VEP and PERG components of 85 patients with MS were analyzed in two groups: 38 patients who had optic neuritis in their history (ON group) and 47 patients who had never had optic neuritis (MS group). The results were compared against a control group of 47 healthy subjects. Results Both VEP and PERG alterations occurred in a greater number of patients than expected, and these alterations were not necessarily linked to ON in the history or a deterioration of visual acuity. Conclusions Both VEP and PERG can detect dysfunction in the visual system in MS, even if the patient has no subjective symptoms. Even if PERG is not routinely used in neuro-ophthalmology, the results suggest that PERG assessment may provide useful information describing the retinal defect in MS.